Experience on mental health protection and integration of health saving technologies in SBI AE OF RR "Regional center for identification and support of gifted children "Stupeni uspeha" - Parkhomenko L. V., Stolnikova V. S., Voronina E. A. (Psychological and Pedagogical Support of Talented Children: Problems, Directions, Approaches, Conditions, 2020)
the experience of SBI AE of RR "Regional center for identification and support of gifted children "Stupeni uspeha" on the organization of preventive measures in crisis and difficulties during pupils’ social adaptation with the usage of health saving technologies is presented in the article.
Keywords: адаптация; одаренность; здоровьесбережение; adaptation; crisis; кризисы; giftedness; health protection; психопрофилактика; mental prevention